Assessment of changes in the structure and distribution of mangroves caused by aquaculture activities at the Bach Dang estuary, Vietnam - Vu Manh, Hung Manh Vu; Pham Quang, Van; Nguyen Manh, Linh; Dau Van, Thao (Vietnam Journal of Marine Science and Technology, 2022)
The development of the movement to change mangroves area for aquaculture has resulted in the loss of a large area of mangroves in Vietnam. The decline of mangroves leads to impacts on natural resources and the environmental and ecological degradation of the area. The aquaculture ponds were built to protect and create a stable environment for livestock, creating a different environment between the inside and the outside of the pond. As a result of the sudden difference in the background, many mangrove species did not adapt quickly leading to death, and many other species came to distribute with new conditions. The paper results are evidence of the impacts of the aquaculture pond filling on the changes in the distribution structure of mangrove vegetation, thereby proposing solutions for sustainable development for the study area.